2021
DOI: 10.1002/adfm.202102983
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric Nanogenerators Derived Self‐Powered Sensors for Multifunctional Applications and Artificial Intelligence

Abstract: With the arrival of the Internet of Things (IoTs) era, there is a growing requirement for systems with many sensor nodes in a variety of fields of applications. The demands for wireless, sustainable and independent operation are becoming more and more important for large‐scale sensor networks and systems. For these purposes, a self‐powered sensory system that can utilize the self‐harvested energy from its surroundings to drive the sensors and directly sense external stimuli has attracted great attention. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
111
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 211 publications
(128 citation statements)
references
References 283 publications
(468 reference statements)
0
111
0
Order By: Relevance
“…The BaTiO 3 nanowire arrays were caped with top electrodes for piezoelectric energy harvesting. [101,102] Zhang et al [103] have reported a topochemical x and y axes represent the [100] and [010] crystallographic directions, respectively, the color bar denotes the angle between the polar vector of the grids and the [100] direction. Reproduced with permission.…”
Section: Progress In Synthesis and Fabrication Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BaTiO 3 nanowire arrays were caped with top electrodes for piezoelectric energy harvesting. [101,102] Zhang et al [103] have reported a topochemical x and y axes represent the [100] and [010] crystallographic directions, respectively, the color bar denotes the angle between the polar vector of the grids and the [100] direction. Reproduced with permission.…”
Section: Progress In Synthesis and Fabrication Methodsmentioning
confidence: 99%
“…Figure 10. a) Microstructures for a [100]-poled PNR-ferroelectric composite at 100 K obtained by phase-field-simulation. b) Enlarged area of (a) with polar vectors.x and y axes represent the[100] and [010] crystallographic directions, respectively, the color bar denotes the angle between the polar vector of the grids and the[100] direction. Reproduced with permission [97].…”
mentioning
confidence: 99%
“…[1][2][3][4][5] In particular, NWs presenting piezoelectric properties appear as promising active nanostructures for a new generation of piezoelectric sensors [6][7][8][9][10] and harvesters. [11][12][13][14][15] Especially, the sub-100 nm-wide NWs present the particularity to exhibit novel properties, non-existing or non-significant at micrometric scales that can lead to a strong modulation/modification of their characteristics. The exaltation of the piezoelectric coefficients, [16][17][18] the modulation of the free carrier concentration 19,20 or the formation of nano-contact at the NW/ electrode interface 21 are examples of these nanoscale phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the rapid development of nano-processing technology, various high-performance miniaturized sensors and devices are proposed in every field of Internet of Things. [1,2] A large part of these nanodevices is distributed in the areas far away from cities or even in extremely low temperature conditions, [3] where the energy is supplied by battery which is costly and environmentally unfriendly. [4,5] As an alternative solution to this challenge, harvesting energy directly from the environment attracts increasing attention recently and a lot of attempts have been made to obtain electricity output with various kinds of generators through utilizing different kinds of power including mechanical energy, [6][7][8] hydraulic energy, [9][10][11] solar energy, [12][13][14] Typical voltage and current responses to the moving of the Cu film along the p-type Si surface are shown in Figure 1c-f.…”
Section: Introductionmentioning
confidence: 99%